Nilai Moral dalam Mitos Naga Mas Danau Ranau pada Masyarakat Desa Sukau - Reihan Franige; Adelio Alvaro; Rahmat Prayogi; Bambang Riadi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The existence of a myth in a society is not only a story, the existence of a myth in a society can also shape moral values and norms for that society. The aim of this research is to find out the morals and behavior of the Sukau village community regarding the myth of the Naga Mas Lake Ranau. This research method is a qualitative descriptive method. This research uses literature study analysis theory, namely by collecting data by understanding and studying theories from various literature related to research. In conclusion, moral values and norms in society can be formed based on an incident or event that develops in a particular society. As happened in Sukau Village, the result of the presence of the golden dragon gave them restrictions on all their activities and the way they behaved, because there was a reciprocal relationship that occurred in all the behavior they carried out.